Effort To Improve Student Learning Activity Using The Google Classroom Application In Class 6 - Jaelani Sidik (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
This study aims to improve student learning activeness in grade 6 using the google classroom application. This research is a classroom action research conducted in 3 cycles. The implementation of each cycle consists of preparation, implementation, observation and reflection. The classroom action research was carried out in grade 6 SDN Kajenengan 02. The study was conducted using the observation sheet using application and student questionnaires on learning activeness. The results of the research in cycle 1 showed that the response to activeness was 84.5% and in cycle 2 it was 91.9%, and there was an increase again in cycle 3, namely 93.3%. From these results it can be concluded that google classroom can improve the learning activeness of grade 6 students at SDN Kajenengan 02.